My baby blue jays - Berendt, John, 1939- (New York : Viking/Penguin Group, 2011)
Author John Berendt chronicles the lives of baby blue jays after he notices a nest outside his office window and follows their lives from eggs to hatchlings to full grown birds.
Keywords: Birds -- New York (State) -- New York -- Juvenile literature; Blue jay -- Juvenile literature; Birds -- Infancy -- Juvenile literature; Blue jay; Birds -- New York (N.Y.)